1996
DOI: 10.1073/pnas.93.18.9942
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The pfmdr1 gene of Plasmodium falciparum confers cellular resistance to antimalarial drugs in yeast cells.

Abstract: The exact role of the pfmdr1 gene in the emergence of drug resistance in the malarial parasite Plasmodium falciparum remains controversial. pfmdr1 is a member of the ATP binding cassette (ABC) superfamily of transporters that includes the mammalian P-glycoprotein family. We have introduced wild-type and mutant variants of the pfmdr1 gene in the yeast Saccharomyces cerevisiae and have analyzed the effect of pfmdr1 expression on cellular resistance to quinoline-containing antimalarial drugs. Yeast transformants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Transformation studies in yeast have shown that pfmdr1 expression results in a reduced sensitivity to MQ and HF whereas expression of a mutant pfmdr1 (carrying two of the three 7G8 mutations) did not. 25 These observations would support the observations reported here.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Transformation studies in yeast have shown that pfmdr1 expression results in a reduced sensitivity to MQ and HF whereas expression of a mutant pfmdr1 (carrying two of the three 7G8 mutations) did not. 25 These observations would support the observations reported here.…”
Section: Discussionsupporting
confidence: 83%
“…15 Interestingly, it is this 7G8 mutation that has been used in the limited transformation studies that have been carried out to date and which support a role for pfmdr1 in resistance. 25,42 One biochemical characteristic that does appear to be associated with CQ resistance in all isolates studied, irrespective of origin, is the ability of verapamil to selectively chemosensitize resistant isolates. 12,43,44 All of the new isolates studied here retained this phenotypic characteristic, including those with intermediate sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In addition, Pgh-1 expression in yeast cells confers cellular resistance to mefloquine, quinine, halofantrine, and quinacrine. 33 If one considers that CQ resistance originated almost simultaneously in Southeast Asia and South America, it is possible that this phenomenon involves multiple transport mechanisms and multiple genes. Recently, field studies 34 have identified a series of mutations of the cg2 gene in CQ resistant P. falciparum, suggesting that this gene is also involved.…”
Section: Malaria Casesmentioning
confidence: 99%
“…9,10 Although the pfmdr 1 gene, but not pfmdr 2, codes for a transmembrane protein capable of transporting drugs across the membrane and point mutations may alter its function, its role in resistance to 4-aminoquinolines and aminoalcohols is still unclear. [11][12][13] A second candidate, cg2 gene, has been recently isolated and characterized. 14 Its functional role is currently unknown.…”
mentioning
confidence: 99%